Product Development and Sensory Acceptability of Malunggay (Moringa oleifera) and Kalabasa (Cucurbita maxima) Ice Cream - Umayam, Mary Anne (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study aimed to develop and evaluate malunggay (Moringa oleifera) and kalabasa (Cucurbita maxima) ice cream as a nutritious traditional dessert. Specifically, it determined the acceptability of malunggay and kalabasa ice cream in terms of taste, texture, color, appearance, general acceptability, economic analysis and market turnover. An experimental research design was employed of four different treatments using varied proportion of ingredients. Sensory evaluation was conducted using the 9-point hedonic scale with 100 respondents. The data gathered were analyzed using descriptive statistics, particularly frequency, percentage, and mean to determine the level of general acceptability of the malunggay and kalabasa ice cream. Results revealed that Treatment 3 is the most acceptable treatment in terms of taste, texture, color, and appearance. The findings suggest that malunggay and kalabasa using treatment 3 can serve as a feasible and nutritious dessert option while maintaining consumer acceptability. It is also a viable food product that can be developed for health-conscious individuals, particularly children and consumers seeking alternative healthy dessert options. Economic analysis of the most acceptable treatment is Treatment 3 revealed a total production cost of ₱348.00 and a net income of ₱102.00 per batch. The computed Return on Investment (ROI) was 29.31%, indicating that the product is economically viable and profitable. Furthermore, Treatment 3 generated a market turnover of ₱450.00 per production batch from the sale of 15 packs at ₱30.00 per pack, demonstrating its potential marketability and revenue-generating capability. These findings suggest that the developed Malunggay and Kalabasa Ice Cream is not only highly acceptable to consumers but also feasible for commercialization.